Correlatıon of Plaque Characterıstıcs wıth Degree of Stenosıs Evaluated by Coronary Angıography Usıng Computed Tomography - Kurnia Arma Wijayanti; Anggraeni Dwi Sensusiati; Anita Widyoningroem (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2026)
Coronary artery disease remains the leading cause of global mortality, and the diagnosis of acute chest pain continues to pose a challenge in emergency care due to the limitations of conventional methods in detecting acute coronary syndrome. Coronary computed tomography angiography (CCTA) has emerged as an efficient non-invasive diagnostic tool for evaluating coronary artery plaque characteristics and stenosis severity. This retrospective study analyzed the correlation between plaque types and degrees of stenosis detected by CCTA in 54 patients presenting with chest pain at Dr. Soetomo General Hospital, Surabaya, during January–December 2023. Plaque morphology was classified into calcified, non-calcified, and mixed types based on CAD-RADS 2.0 criteria. Data were analyzed using Spearman’s correlation test. Mixed plaques were the most frequently observed (120 samples), followed by calcified (78 samples) and non-calcified (71 samples). Moderate stenosis was most commonly associated with mixed plaques, while severe stenosis was most frequently found in association with non-calcified plaques. Statistical analysis revealed a significant and very strong correlation between plaque type and stenosis severity in eight coronary segments. These findings highlight the diagnostic value of CCTA in evaluating plaque morphology and stenosis, particularly in identifying mixed plaques that are closely linked to more severe coronary obstruction. The results support the role of CCTA as a critical tool in the diagnostic workup of patients with acute chest pain.